1979
DOI: 10.1111/j.1432-1033.1979.tb12985.x
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin D of Rat Spleen Affinity Purification and Properties of Two Types of Cathepsin D

Abstract: Two types of cathepsin D were purified from rat spleen by a rapid procedure involving an acid precipitation of tissue extract, affinity chromatography with pepstatin-Sepharose 4B and concanava h -A -Sepharose 4B, and chromatography on Sephadex G-100 and DEAE-Sephacel. The purified major enzyme (85 % of the cathepsin D activity after DEAE-Sephacel chromatography), termed cathepsin D-I, represented about a 1000-fold purification over the homogenate and about a 20% recovery. The purified minor enzyme (15 %), term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…In-1 (anti-mouse Ii antibody), anti-mouse Lamp-2 antibody, and anti-mouse transferrin receptor (TfR) antibody were purchased from PharMingen (San Diego, CA). Polyclonal antibodies against purified rat spleen CE and CD were raised in rabbits and purified by affinity chromatography as described previously (32)(33)(34). CE and CD were purified from rat spleen according to the previously described methods (32,33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-1 (anti-mouse Ii antibody), anti-mouse Lamp-2 antibody, and anti-mouse transferrin receptor (TfR) antibody were purchased from PharMingen (San Diego, CA). Polyclonal antibodies against purified rat spleen CE and CD were raised in rabbits and purified by affinity chromatography as described previously (32)(33)(34). CE and CD were purified from rat spleen according to the previously described methods (32,33).…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal antibodies against purified rat spleen CE and CD were raised in rabbits and purified by affinity chromatography as described previously (32)(33)(34). CE and CD were purified from rat spleen according to the previously described methods (32,33). Cathepsin B (CB) was purified form rat kidney as described (35).…”
Section: Methodsmentioning
confidence: 99%
“…Yamamoto et al 36 ) reported that 10mMf3-Me did not activate the cathepsin D of rat spleen, but it did activate 40% activity of that from carp muscle. 29,30) However, 1 mM f3-Me partially inhibited the activity of cathepsin D from banded shrimp i muscle.…”
Section: Effects Of Reductants and Sodium Dodecyl Sulfate (Sds)mentioning
confidence: 99%
“…Na +, K +, Ca z +, Zn z +, Ni 2 +, and Cu z + ions activated the cathepsin D from milkfish but did not affect that from mackerel (Table V). According to Takeda et al 45 ) and Yamamoto et al,36,39) cathepsin D from rat spleen and human erythrocyte membrane acid proteinase (EMAP) were inhibited by Hg2 + and Fe 3 +. The Mgz+, Ca 2 +, and Ni 2 + (lOmM) did not affect the activity of cathepsin D from rat spleen, but significantly activated that from tilapia muscle.…”
Section: Effects Of Metal Ionsmentioning
confidence: 99%
“…The following antibodies were used in this study: Rabbit antiserum against mouse cathepsin D (Pohlmann et al, 1995), rabbit antiserum against rat liver cathepsin D purified from lysosomal contents by affinity chromatography on pepstatin A-sepharose as described (Yamamoto et al, 1979), affinity-purified rabbit antibody against the cytoplasmic tail of MPR46 (MSC1; Klumperman et al, 1993), rabbit antiserum against human MPR46 (II-4; Wenk et al, 1991), rabbit antiserum against rat MPR300 (I-5; Claussen et al, 1995), mouse mAb against ␥-adaptin (Transduction Laboratories, Lexington, KY), and rat monoclonal antibodies against LAMP-2 (ABL93) and LAMP-1 (1D4B; Developmental Studies Hybridoma Bank, Iowa City, Iowa).…”
Section: Primary Antibodiesmentioning
confidence: 99%